Ruining the algorithm: Sound, technology, and collaborative networks in Latin American sonic experimentalism. - García Castilla, Jorge David (Organised Sound, 2026)
This article addresses sonic experimentalism in Latin America from a critical perspective based on a review of artistic projects that have been active in recent years in different countries of the region. Its main objective is to discuss whether there are features that can be conceived as characteristic of Latin American sonic experimentalism, whether it is relevant to define issues that affect the people and communities that practice it in a cross-cutting manner, and, if so, whether it is feasible to talk about strategies that bring together people and groups who, although they work in different countries and conditions, consider themselves as part of the same community. Through the three axes chosen to structure this article (sonority, technology, and collaborative platforms), several aspects will be addressed that link a significant number of sound and experimental music artists in different locations within the territory in question. This will lead to a discussion about identity expressed in sound practices, using a cultural studies approach. By foregrounding voices that "ruin the algorithm" of coloniality, this research enriches Latin American sound studies debates and seeks to contribute to the study of experimentalism in the Global South.